The Role of Civic Responsibility In Educating Youth In A Healthy Spiritual Environment In An Information Society - Madatovich, Ruzimurodov (Pubmedia Social Sciences and Humanities, 2025)
The article discusses the large-scale work being carried out in our country to ensure a healthy lifestyle for young people, to educate them as physically and spiritually perfect people. In this regard, attention is paid to the issue of ensuring the stability of the spiritual environment based on the establishment of a healthy lifestyle in young people. It is also scientifically substantiated that the neighborhood environment plays a significant role in protecting young people from the influence of information attacks.The influence of family, community, and educational institutions in creating and maintaining a spiritually enriching environment is also discussed. Moreover, the article highlights the importance of safeguarding youth against the negative effects of information attacks through educational, cultural, and philosophical approaches rooted in national and universal values.Emphasis is placed on cultivating ideological immunity, moral consciousness, national identity, and historical memory among youth as vital elements of civic responsibility.